2010
DOI: 10.4049/jimmunol.0903673
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Cell-Derived CXCL12 and CCL8 Cooperate To Support Increased Development of Regulatory Dendritic Cells Following Leishmania Infection

Abstract: Material Supplementary 3.DC1http://www.jimmunol.org/content/suppl/2010/07/12/jimmunol.090367

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Recently, Nguyen et al showed that infection with L. donovani induces the expression of CCL8 by murine stromal cells promoting regulatory dendritic cell differentiation and suggested that the aberrant production of this chemokine may be associated with persistent infection during chronic inflammation (36). The present findings for human dermal leishmaniasis caused by L. panamensis demonstrate that infection with strains isolated from patients with chronic disease, but not from self-healing individuals, induced CCL8 at the gene and protein levels, in line with maintenance of a chronic inflammatory response.…”
Section: Fig 3 Mlmt Analysis Of L Panamensis Strains Isolated From Pmentioning
confidence: 99%
“…Recently, Nguyen et al showed that infection with L. donovani induces the expression of CCL8 by murine stromal cells promoting regulatory dendritic cell differentiation and suggested that the aberrant production of this chemokine may be associated with persistent infection during chronic inflammation (36). The present findings for human dermal leishmaniasis caused by L. panamensis demonstrate that infection with strains isolated from patients with chronic disease, but not from self-healing individuals, induced CCL8 at the gene and protein levels, in line with maintenance of a chronic inflammatory response.…”
Section: Fig 3 Mlmt Analysis Of L Panamensis Strains Isolated From Pmentioning
confidence: 99%
“…Furthermore, they prompted hematopoietic progenitors to differentiate toward regulatory IL-10 producing tDCs (27). During Leishmania infection, splenic stromal cells upregulated chemokine (C–X–C motif) ligand 12 (CXCL12) and CCL8 to specifically attract hematopoietic precursors and induced tDC differentiation in situ (152). Importantly, tDCs have been identified under steady state in lung (28), spleen (26, 27, 29), and liver (30).…”
Section: Interactions Between Tdcs and Immune Or Stromal Cells For Tomentioning
confidence: 99%
“…To date, stromal cell-induced rDCs have been reported in murine spleen (Svensson et al, 2004; Zhang et al, 2004; Tang et al, 2006; Nguyen Hoang et al, 2010; Xu et al, 2012), liver (Xia et al, 2008), kidney (Huang et al, 2009), lung (Li et al, 2008), and tumor tissue (Liu et al, 2009). Despite their divergent tissue localization, the majority of studies reporting stromal cell-induced rDCs have characterized them as populations of CD11c lo MHCII lo/int CD11b + cells, based on surface protein expression assessed by flow cytometry.…”
Section: Regulatory Dcs: Characterization and Functionmentioning
confidence: 99%
“…One exception is experimental visceral leishmaniasis (EVL), a chronic infection caused by the intracellular parasite L. donovani (Kaye et al, 2004). Splenic stromal cells from mice infected with L. donovani have an enhanced capacity to direct hematopoietic progenitors toward a rDC phenotype in vitro (Svensson et al, 2004), a process at least in part dependent upon infection-modulated levels of the chemokine CCL8 (Nguyen Hoang et al, 2010). The precise mechanisms by which infection itself enhances the capacity for stromal cells to support rDC induction during chronic inflammation are not known, but as stromal cells are targets of Leishmania infection (Bogdan et al, 2000) it is feasible that direct parasite modulation of stromal cell function may represent a strategy for manipulating host defense mechanisms in favor of the invading pathogen (Svensson and Kaye, 2006).…”
Section: Specific Contexts Leading To the Induction Of Rdcs By Stromamentioning
confidence: 99%
See 1 more Smart Citation